1998
DOI: 10.1016/s0741-5214(98)70294-0
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopically assisted abdominal aortic aneurysm repair: First 20 cases

Abstract: Laparoscopically assisted AAA repair is technically challenging but feasible. Potential advantages may be early removal of nasogastric suction, shorter intensive care unit and hospital stays, and prompt return to full functional status. The hemodynamic data obtained from the pulmonary artery catheter and transesophageal echocardiogram during pneumoperitoneum suggest that transesophageal echocardiography may be sufficient for evaluation of volume status along with the added benefit of detection of regional wall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
46
0
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 14 publications
1
46
0
2
Order By: Relevance
“…At this writing, we have treated 31 patients with laparoscopic procedures for aortoiliac occlusive disease under a research protocol [13]. Others also have reported animal and clinical works performed either totally laparoscopically or laparoscopically assisted with good results [2,3,14,17,18,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At this writing, we have treated 31 patients with laparoscopic procedures for aortoiliac occlusive disease under a research protocol [13]. Others also have reported animal and clinical works performed either totally laparoscopically or laparoscopically assisted with good results [2,3,14,17,18,20].…”
Section: Discussionmentioning
confidence: 99%
“…One death occurred from ischemic colitis after IMA ligation. Kline et al [17] reported 20 cases of laparoscopically assisted abdominal aortic aneurysm repair. One patient underwent a Hartmann's procedure for postoperation ischemia of the left colon.…”
Section: Discussionmentioning
confidence: 99%
“…Die Operationstechnik erfordert eine gewisse Umstellung ist jedoch der offenen Technik vergleichbar. Wegen ihrer geringeren Wundkomplikationen und besseren kosmetischen Ergebnisse verdient sie eine größere Bedeutung in der Koronarund peripheren Bypasschirurgie [2,10,12,23,24]. Eine andere Situation wird sich einstellen, wenn durch die Entwicklung neuerer laparoskopischer Nahttechniken und den Einsatz von Operationsrobotern eine signifikante Reduktion von Operations-und Anastomosenzeiten möglich ist [43].…”
Section: Diskussionunclassified
“…Initially, only dissection was performed endoscopically, but complete laparoscopic vascular procedures for abdominal aneurysm repair and occlusive disease have been reported [1,3,5,8,10,11]. Although the safety and feasibility of these procedures have been demonstrated, all authors stress the importance of training and experience to reduce operating time and complications [1,3,5,8].…”
mentioning
confidence: 99%